Unilateral termination of employment of pensionable workers held unconstitutional - Hude, Zarja (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
During the second wave of the COVID-19 epidemic, the Slovenian legislator adopted the Act Determining Intervention Measures to Assist in Mitigating the Consequences of the Second Wave of COVID-19 Epidemic (Zakon o interventnih ukrepih za pomoč pri omilitvi posledic drugega vala epidemije COVID-19). According to the draft law, the aim of the emergency piece of legislation was to mitigate and eliminate negative effects of the COVID-19 epidemic on businesses, the labour market, the healthcare system and social security schemes. Nevertheless, the intervention act also amended provisions concerning the termination of employment contract by introducing a new exception to the requirement of a substantiated valid (business) reason for dismissing a worker. The employers in both private and public sector were now eligible to terminate the employment contracts of workers who met the conditions for acquiring the right to an old-age pension without stating or justifying any valid (business) reason whatsoever. The article examines the judgement of the Constitutional Court of the Republic of Slovenia reached in a case put forward by Slovenian trade unions and the Advocate of the Principle of Equality, with an emphasis on the courts somewhat formalistic approach to what could have been a major antidiscrimination decision concerning old-age.
Keywords: odpoved pogodbe; pogodba o zaposlitvi; sodna praksa; starost; upokojitev; ustava